Persepsi agentik individu untuk mencapai prestasi pribadi dalam aktivitas karir: riset pendahuluan - Alfaiz Alfaiz; Hengki Yandri; Yuzarion Yuzarion; Luh Putu Sri Lestari; Eka Heriyani (Psychocentrum Review, 2019)
This research aim to observe and understanding a condition of employee’s individual agentic on pursue their achievement in career activities. Individual agentic was personal psychological condition and competence to planning, organize an action and reflection. It’s manifested in four aspects such intentional, forethought, self reactiveness and self reflection. This data was collected through quantitative descriptive method with 200 respondents, in this collection found 135 repondents has a low agentic perception and 65 respondents has high on agentic perception in career activities. This findings majority respondents has a lack of forethought competence and self reflection in their career activities, there are 38 teachers has low level, 33 lecturers in low level, 31 lecturers and 33 goverment employee low level in forethought. It should be adjust through exercise of agentic awareness that shaping their purposefull life and manageble thinking with Agentic Autonomous Thinking and Behavior Strategy (AATBS), this strategy developed by researcher through synthesize a concept of personal agency will be described in this article as prelude to explain a condition of respondents in agentic perspective.